Implementasi Pembiayaan Ijarah Muntahiya Bittamlik (Studi Kasus Pada Koperasi Syariah Ar-Rahmah Gayabaru) - Mutmainah Juniawati (Institut Agama Islam Agus Salim Metro Lampung, 2022)
This study to determine the implementation of the financing of ijarah muntahiya bittamlik in the sharia cooperative of Ar-Rahmah Gayabaru. The research method used is descriptive qualitative. Collecting data using interviews, documentation, and observation. Data analysis using qualitative analysis techniques with the way of thinking inductive. Benefit from this research, namely to become material information for add sciences about institution finance sharia especially on sharia cooperative of Ar-Rahmah Gayabaru in the role which given to public. Results from analysis concluded that by implementation stages- the stages of the ijarah muntahiya bittamlik procedure in accordance with sharia principles, pillars ijarah muntahiya bittamlik, the flow of the ijarah muntahiya bittamlik contract, it's appropriate with theory. Although there are still some implementations of ijarah muntahiya bittamlik which not in accordance with sharia, or not in accordance with the theory, of them that is : mechanism implementation ijarah muntahiya bittamlik the discrepancy with Nur.S.Buchori's book is related to documentation on implementation no there is letter application realization ijarah muntahiya bittamlik and the absence of a contract for the transfer of the object of the lease, the terms cooperative sharia Ar-Rahmah Gayabaru on implementation not in accordance with PBI No. 7/46/PBI/2005 because it has not stated the conditions for cooperatives sharia Ar-Rahmah Gayabaru the if implementation ijarah muntahiya bittamlik can only conducted after ijarah contract fulfilled